Design of a navigation and localization system for an AI-enabled underwater robot - Wong, Kelvin Jin Tong (2019)
Navigation has constantly been a challenge for unmanned vehicles operation. In underwater environment, the complexity for navigation of unmanned underwater vehicle’s increase exponentially because of the working environment and the constraint on GPS signals. Thus, the cost for navigation and localization systems for underwater operation has been consistently high and has limits the use for small and medium-sized enterprises. Above all, the various methods introduced for navigation and localization in unmanned underwater vehicles have its limitations in practical performance. Ultra-Wide Band (UWB) has progressively developed application on navigation and localization for air and land operation. Meanwhile, the publication of UWB technology in underwater operation has received very little attention because of their limitation with inherent errors in water medium. Yet, there is an opening possibility for UWB technology to perform navigation and localization in air for unmanned underwater vehicles. There is no evident how the setup would affect the navigation and localization accuracy. This project will design, develop and demonstrate the practical performance of a commercial UWB product and asses the observable errors. Progressively, to determine UWB suitability as a sustainable low-cost alternative for current navigation and localization systems for manned underwater vehicles.